Sistem Rekrutmen dan Penempatan Karyawan PT. Bank Rakyat Indonesia (Persero) Tbk. Kota Palangka Raya - H, Fendy Hariatama; Sri Rohaetin; Alexandro, Rinto; Grace Evelina Buji; Rahman, Rahman (FKIP, Universitas Palangka Raya, 2024)
In this study researchers used qualitative research, where qualitative research is a research method used to research on natural object conditions, where the researcher is the key instrument, data collection techniques are triangulated (combined), data analysis is inductive, and qualitative research results emphasize meaning rather than generalization. By using this qualitative method, researchers will make observations, in the form of interviews and review documents to provide a direct description of the nature of the respondent, namely the Analysis of the Recruitment System and Placement of Employees in Working at BRI BANK Jalan Imam Bonjol Kota Palangka Raya. Recruitment itself is a process of attracting, holding, and searching and finding a group of candidates who submit applications which can later fill vacant positions in an organization or company. The purpose of the recruitment system itself is to meet the needs of a company or organization regarding the human resources contained in the company so that later get human resources that are truly qualified. Analysis of the recruitment and placement system of employees in the context of Bank BRI (PT Bank Rakyat Indonesia Tbk) is an important process to improve efficiency and effectiveness in the process of developing human resources. The results show that the recruitment process that is carried out by the company is not a